INFLUENCE OF FAT CONTENT ON THE QUALITY AND SHELF LIFE OF CURED SARDINES. - DEVADASAN, K; MURALIDHARAN, V; JOSEPH, GEORGE (Fishery Technology, 2017)
The paper presents results of studies on the effect ofseasonal variations in the fat content on the quality and shelflife of dry cured, pickle cured and smoke cured oil sardines.The merits and defects of each method of curing duringdifferent seasons are discussed